Methods for caries prevention in adults among dentists from a brazilian community - da Silva Tagliaferro, Elaine Pereira [UNESP]; da Silva, Silvio Rocha Correa [UNESP]; Rosell, Fernanda Lopez [UNESP]; Junior, Aylton Valsecki [UNESP]; Riley, Joseph L.; Gilbert, Gregg H.; Gordan, Valeria Veiga (Universidade Estadual de Campinas, 2020)
Little is known about dental practice patterns of caries prevention in adults among Brazilian dentists. Aim: To quantify procedures used for caries prevention for adult patients among dentists from a Brazilian community. Methods: Dentists (n=197) who reported that at least 10% of their patients are more than 18 years old participated in the first Brazilian study that used a translated version of the Assessment of Caries Diagnosis and Caries Treatment from the U.S. National Dental Practice-Based Research Network. A questionnaire about characteristics of their practice and patient population were also completed by the dentists. Generalized linear regression models and a hierarchal clustering procedure were used (p<0.05). Results: In-office fluoride application was the preventive method most often reported. The main predictors for recommending some preventive agent were: female dentist (dental sealant; in-office fluoride; non-prescription fluoride) and percentage of patients interested in caries prevention (dental sealant; in-office fluoride; non-prescription fluoride). Other predictors included private practice (dental sealant), percentage of patients 65 years or older (in-office fluoride), graduation from a private dental school (non-prescription fluoride), years since dental school graduation (chlorhexidine rinse) and using a preventive method (recommending sealant/fluoride/chlorhexidine rinse/sugarless, xylitol gum). Cluster analysis showed that dentists in the largest subgroup seldom used any of the preventive agents. Conclusion: Dentists most often reported in-office fluoride as a method for caries prevention in adults. Some practitioner, practice and patients' characteristics were positively associated with morefrequent use of a preventive agent.
Keywords: Dental caries; Physicians; Practice patterns; Preventive dentistry